Evaluating the Potential of Augmented Reality Interfaces for Exploring Underwater Historical Sites - Čejka, Jan; Mangeruga, Marino; Bruno, Fabio; Skarlatos, Dimitrios; Liarokapis, Fotis (My University, 2021)
Underwater cultural heritage sites represent an attractive and exciting experience for diving tourists, even if often it is complicated for them to understand the significance and value of the remains that are usually strongly damaged and covered by the marine organisms. Thanks to the recent advancements in technologies that overcome these problems, augmented reality is nowadays possible even in such harsh conditions, opening new possibilities for enhancing the diver's experience. However, no user study has formally evaluated the usefulness and usability of augmented reality in open sea underwater environments. This paper presents two novel solutions for underwater augmented reality: a compact marker-based system for small areas, and a complex acoustic system for large areas. Both of them were deployed at an underwater cultural heritage site and evaluated by ten divers in experiments analyzing their perception and remembrance, interests, and user experience. For comparison, the same study was also performed with non-divers assessing the marker-based system on land. Results show that both systems allow divers to encounter new and exciting moments and provide valuable insights for underwater augmented reality applications.
Keywords: Augmented reality; Cultural heritage; Sensor fusion; Underwater; User experience; User testing